PENGARUH CORPORATE GOVERNANCE, LEVERAGE TERHADAP MANAJEMEN LABA PADA PERUSAHAAN PERBANKAN (Students' Journal of Accounting and Banking, 2012)
The purpose of this study was to examine the effect of the implementation of corporate governance as measured by the proportion of independent commissioners, the size of the board of directors, audit committees and leverage existence of earnings management measures. the use of discretionary accruals as a proxy for earnings management is calculated by using the modified Jones model (Dechow et al., 1995).In this study the sample used is a banking company which has gone public on the Indonesia Stock Exchange (BEI) in 2008-2010. This study uses data collection by purposive sampling. With these methods the number of samples obtained in this study as much as 72 banking companies from 24 banking companies each year.By using multiple linear regression analysis tool, obtained the result that a variable proportion of independent commissioners positive effect on earnings management. Existence of audit committee variables negatively affect earnings management. Variable board size and leverage are not negatively affect earnings management.Keywords: corporate governance, leverage, banks, profit management.